Synthesis of Cyclopropyl- and Cyclobutylpiperidines: Advanced Building Blocks for Drug Discovery - Vyzir, Ivan I.; Iminov, Rustam T.; Tverdokhlebov, Anton; Tolmachev, Andrey A.; Shcherbatiuk, Andriy V.; Mykhailiuk, Pavel K.; Biitseva, Angelina V. (Synthesis, 2015)
A library of cyclopropyl- and cyclobutylpiperidine derivatives were synthesized from commonly available starting materials through Wittig reactions.
Keywords: amines; azetidines; piperidines; phosphonium salts; Wittig reaction